Cerebellar Atrophy with Phenytoin and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Cerebellar size measured by MRI was studied in a group of 36 adults (21 to 54 years, mean age 34 years) with intractable partial epilepsy treated with phenytoin longer than 4 years at the Epilepsy Center of the Long Island Jewish Medical Center, New Hyde Park, NY.